Inherited bone marrow failure syndromes. An overview (Journal of Pathology of Nepal, 2021)
Inherited bone marrow failure syndromes are a diverse set of genetic disorders characterized by insufficient blood cell production leading to cytopenias/pancytopenia. Bone marrow failure can be restricted to one or two blood cell lineages, with symptoms specific to the particular cell lineage or it can affect all cell lineages, causing clinical symptoms similar to aplastic anemia. Inherited bone marrow failure syndromes are genetically heterogeneous diseases resulting from germline mutations that affect key cellular pathways namely ribosomal biogenesis, telomerase biology, DNA repair, and structural proteins. Common Inherited bone marrow failure syndromes are Diamond-Blackfan anemia, Fanconi anemia, Dyskeratosis Congenita, and Shwachman-Diamond syndrome. These different syndromes have variable prognoses and risks of developing hematological or solid malignancies. Thus the accurate diagnosis of these diseases differentiating it from other Inherited bone marrow failure syndromes and other causes of bone marrow failure is of utmost importance for management and surveillance of long-term squeal of the disease. Other causes of BMF can be acquired. The most common forms of Bone marrow failure can occur from chemicals, radiation, drugs, viral infections, immune disorders, myelodysplastic syndrome, paroxysmal nocturnal hemoglobinuria, or large granular lymphocytic leukemia. Moreover, these Inherited bone marrow failure syndromes are often heritable, affecting other family members, thus requiring insightful genetic counseling. This review discusses the frequent Inherited bone marrow failure syndromes along with their differential diagnosis.